2018
DOI: 10.1001/jamainternmed.2018.3766
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Group-Administered Behavioral Treatment on Urinary Incontinence in Older Women

Abstract: IMPORTANCE Urinary incontinence (UI) guidelines recommend behavioral interventions as first-line treatment using individualized approaches. A one-time, group-administered behavioral treatment (GBT) could enhance access to behavioral treatment.OBJECTIVE To compare the effectiveness, cost, and cost-effectiveness of GBT with no treatment for UI in older women. DESIGN, SETTING, AND PARTICIPANTS Multisite randomized clinical trial (the Group LearningAchieves Decreased Incidents of Lower Urinary Symptoms [GLADIOLUS]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
1
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(87 citation statements)
references
References 40 publications
2
73
1
10
Order By: Relevance
“…We cannot comment either on the extent to which the bladder education received during the initial trial affected their willingness to continue exercises or their behavior in some other way. Diokno et al 20 showed a modest improvement in continence with a single session of group education. As in the earlier trial, 8 the primary outcome measure for the follow‐up study entailed the participant tying a knot in a ribbon each time she leaked urine.…”
Section: Discussionmentioning
confidence: 98%
“…We cannot comment either on the extent to which the bladder education received during the initial trial affected their willingness to continue exercises or their behavior in some other way. Diokno et al 20 showed a modest improvement in continence with a single session of group education. As in the earlier trial, 8 the primary outcome measure for the follow‐up study entailed the participant tying a knot in a ribbon each time she leaked urine.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent randomized controlled trial (RCT) of 307 older adults, FlexToBa was found to be “enjoyable,” safe and efficacious for improving balance and function . A DVD on bladder training with urge suppression and behavioral measures was developed by a nurse practitioner with extensive experience in behavioral management of UI . Finally, the intervention included a home visit during which a trained study coordinator provided written recommendations for home improvement using a checklist for falls prevention in older adults developed by the Center for Disease Control and Prevention (CDC)…”
Section: Methodsmentioning
confidence: 99%
“…A competency-based approach and case method approach encourages everyone to actively participate and use the group as a learning tool and have much greater motivational power than other methods [21]. The GLADIOLUS study demonstrated that one-time use of Group Behavioral Therapy (GBT) is moderately effective and cost-saving for reducing frequency, severity, and improved quality of life [34]. The competency-based approach and case methods approaches have been demonstrated as an effective strategy in modifying attitudes, knowledge, and skills that are generally more effective than traditional, passive modes of teaching.…”
Section: Competency-based and Case-based Approachesmentioning
confidence: 99%